The Potential of Leaf Organs from Sorghum Ratoon Plants Cultivated in Inceptisol Land as Organic Herbicides - Edi Susilo; Susi Handayani; Andreani Kinata; Hesti Pujiwati; Wismalinda Rita (International Journal of Integrative Sciences, 2023)
The sorghum plant is a multi-functional plant, namely as food, feed, organic fertilizer, and organic herbicide. As an organic herbicide, sorghum plants contain allelopathy. Water extracts derived from the leaf organs of sorghum ratoon plants are interesting things to study related to the effect of allelopathy on test plants. The research aims to determine the potential of extracts derived from the leaf organs of ratoon plants of several sorghum varieties produced on inceptisols land as organic herbicides. The research was conducted from March to September 2022 at Kandang Mas, Kampung Melayu District, Bengkulu City (preparation of ratoon plants). In May 2023 at Bentiring Permai, Muara Bangkahulu District, Bengkulu City (bioassay test). The study used a single-factor, completely randomized design. The treatment of extracts derived from leaf organs, the level is control, leaves of ratun plant variety Numbu, leaves of ratun plant variety Super 1, and leaves of ratun plant variety Super 2. Using the bioassay method in Petri dishes repeated four times. Each petri dish was given 10 ml of extract, sown with 20 mung bean seeds of Vima 3 variety, and incubated for three days. The results showed that the water extract from the leaf organ of the ratoon plant variety Super 1 produced the highest inhibition against the test plant. The leaf organ of the sorghum ratoon plant variety Super 1 has better potential as an organic herbicide